Muslims at the margins of Europe : Finland, Greece, Ireland and Portugal - Martikainen, Tuomas; Mapril, José; Khan, Adil Hussain (Muslim Minorities, 2019)
This volume focuses on Muslims in Finland, Greece, Ireland and Portugal, representing the four corners of the European Union today. It highlights how Muslim experiences can be understood in relation to a country's particular historical routes, political economies, colonial and post-colonial legacies, as well as other factors, such as church-state relations, the role of secularism(s), and urbanisation. This volume also reveals the incongruous nature of the fact that national particularities shaping European Muslim experiences cannot be understood independently of European and indeed global dynamics. This makes it even more important to consider every national context when analysing patterns in European Islam, especially those that have yet to be fully elaborated. The chapters in this volume demonstrate the contradictory dynamics of European Muslim contexts that are simultaneously distinct yet similar to the now familiar ones of Western Europe's most populous countries.